2006
DOI: 10.1371/journal.pmed.0030265
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cortical Development after Premature Birth Shown by Altered Allometric Scaling of Brain Growth

Abstract: BackgroundWe postulated that during ontogenesis cortical surface area and cerebral volume are related by a scaling law whose exponent gives a quantitative measure of cortical development. We used this approach to investigate the hypothesis that premature termination of the intrauterine environment by preterm birth reduces cortical development in a dose-dependent manner, providing a neural substrate for functional impairment.Methods and FindingsWe analyzed 274 magnetic resonance images that recorded brain growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
294
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 367 publications
(325 citation statements)
references
References 46 publications
24
294
2
5
Order By: Relevance
“…Numerous works have been published in the literature that have improved our understanding of the perinatal brain (Ball et al, 2013b(Ball et al, , 2017Counsell et al, 2013;Doria et al, 2010;Kapellou et al, 2006;Keunen et al, 2017;Krishnan et al, 2017;Xue et al, 2007;Dubois et al, 2008a,b;Pienaar et al, 2008;RodriguezCarranza et al, 2008;Awate et al, 2010;Hill et al, 2010;Rathbone et al, 2011;Moeskops et al, 2013;Li et al, 2014b,a;Meng et al, 2014;Nie et al, 2014;Wang et al, 2014;Engelhardt et al, 2015;Lefevre et al, 2015;Li et al, 2015b;Moeskops et al, 2015;Li et al, 2016;Hazlett et al, 2017). Study- ing the developing connectome will open up many opportunities in future, not least because neonatal brain imaging data is changing rapidly, at scales that can be clearly resolved using current MRI technology.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous works have been published in the literature that have improved our understanding of the perinatal brain (Ball et al, 2013b(Ball et al, , 2017Counsell et al, 2013;Doria et al, 2010;Kapellou et al, 2006;Keunen et al, 2017;Krishnan et al, 2017;Xue et al, 2007;Dubois et al, 2008a,b;Pienaar et al, 2008;RodriguezCarranza et al, 2008;Awate et al, 2010;Hill et al, 2010;Rathbone et al, 2011;Moeskops et al, 2013;Li et al, 2014b,a;Meng et al, 2014;Nie et al, 2014;Wang et al, 2014;Engelhardt et al, 2015;Lefevre et al, 2015;Li et al, 2015b;Moeskops et al, 2015;Li et al, 2016;Hazlett et al, 2017). Study- ing the developing connectome will open up many opportunities in future, not least because neonatal brain imaging data is changing rapidly, at scales that can be clearly resolved using current MRI technology.…”
Section: Discussionmentioning
confidence: 99%
“…While axons continue to grow, facilitating major connections in the white matter to find their cortical targets, the overlying cortex transforms its relatively smooth surface into a highly convoluted mantle with secondary and tertiary sulci that resembles the adult human brain (Stiles and Jernigan, 2010;Striedter et al, 2014). MRI studies in preterm infants have reported a five-fold increase in cortical surface area and doubling of cortical curvature measures in the timeframe that coincides with the third trimester of pregnancy (Ajayi-Obe et al, 2000;Dubois et al, 2008;Kapellou et al, 2006;Moeskops et al, 2015).…”
Section: Late Fetal Periodmentioning
confidence: 99%
“…A normal cerebral ultrasound scan and larger OFC at 30 months corrected age were both associated with higher reading and mathematics scores. This may reflect perinatal insults to the developing brain or the impact of EP birth on normal brain growth and development (Kapellou et al, 2006;Peterson et al, 2000Peterson et al, , 2006.…”
Section: Predicting Educational Outcomes In Children Born Epmentioning
confidence: 99%